"Jen mě prosili, abych šel ven a zavolal na Božího syna, aby jim přivedl nějaké tuleně." Grónská zkušenost misionářů obnovené Jednoty Bratrské v 18. století - Hojda, Zdeněk; Křížová, Markéta (Univerzita Karlova, Filozofická fakulta, 2017)
The beginning of the 18th century saw a revival of interest in distant Greenland, a possession of the Kingdom of Denmark. The early pioneers were missionaries, first the Danish Lutheran priest Hans Egede and after 1733, members of the renewed Brüder-Unität (Moravian Church). From Moravia came also the three founders of the Moravian mission, later the settlement of New Herrnhut in the place of the present-day capital Nuuk. Their efforts are presented on the basis of an extensive documentation preserved in the archives of the Moravian Church in Herrnhut, from the first difficult years to their successes, crowned after a half a century of work by the founding of a third Moravian settlement in Greenland. The trials of the mission were occasioned not only by the extreme wildness of the island, but especially by the barrier of a completely different language, thinking, lifestyle and experience separating the missionaries from the native Inuit people. 25 34